Immunocyto- and histochemical profiling of nucleostemin expression: marker of epidermal stem cells? - Lacina, Lukás; Smetana, Karel; Dvoránková, Barbora; Stork, Jirí; Plzáková, Zuzana; Gabius, Hans-Joachim (Journal of dermatological science, 2006)
BACKGROUND AND OBJECTIVE: Because the nucleolar protein nucleostemin is present in bone marrow and neuronal stem cells and malignancies originating thereof we monitored its expression in frozen sections from normal human epidermis, basal cell carcinomas, cultured keratinocytes and cells of the squamous carcinoma line FaDu. In addition, probing the value of this protein as a marker of epidermal stem cells was an aim of this study. MATERIALS AND METHODS: To further characterize cell features we added analysis of expression of keratins 10 or 19 as markers of terminal differentiation and Ki67 as marker of proliferating cells as well as three adhesion/growth-regulatory galectins. RESULTS: Immunohistochemical monitoring revealed expression of nucleostemin in cells of both Ki67-positive and -negative nuclei regardless of the K10-expression status. Cultured keratinocytes were positive, when they were prepared from hair follicles and cultured in the presence of feeder cells. A small population of these nucleostemin-positive cells also expressed galectin-1 but not galectins-3 and -9 in their nucleoli. Part of these cells also expressed keratin 19. FaDu cells were strongly positive, illustrating expression in malignant cells which require no feeder layer. Of note, the number of galectin-1-positive nucleoli was reduced in the course of culture. CONCLUSION: Nucleostemin positivity cannot be considered as marker for stem cells in skin sections. In cultured cells, nucleostemin is expressed in a distinct population of the epidermal cells from hair follicle kept in the presence of a feeder layer, intimating an association of nucleostemin expression with this type of epithelio-mesenchymal interaction which is not essential during propagation of malignant cells.
Keywords: regulace genové exprese u nádorů; antigen Ki-67; Nuclear Proteins; transportní proteiny; Carcinoma, Squamous Cell; epidermis; Epidermis; Stem Cells; biologické markery; jaderné proteiny; bazocelulární karcinom; Biomarkers; Gene Expression Regulation, Neoplastic; Keratin-9; Epidermal Cells; proteiny vázající GTP; Immunohistochemistry; lidé; epidermální buňky; Galectins; GTP-Binding Proteins; kmenové buňky; nádorové buňky kultivované; kultivované buňky; imunohistochemie; nádory kůže; galektiny; regulace genové exprese; Carrier Proteins; Cells, Cultured; Keratin-10; keratin-10; Tumor Cells, Cultured; Skin Neoplasms; spinocelulární karcinom; Carcinoma, Basal Cell; keratin-9; Ki-67 Antigen; Gene Expression Regulation; Humans